Responses of crops for diverse soil phosphorus conditions and potential crops for phytoextraction of enriched soil phosphorus - Mayakaduwa, Mayakaduwege Amoda Priyangi; Yusop, Mohd Rafii; Ismail, Roslan; Liyanage, Liyana Rallage Mahesh Chaminda; Rupasinghe, Minninga Geethika Neranjani; Musa, Mohamed Hanafi (Taylor and Francis, 2024)
Phytoextraction is an attractive method to extract excess soil phosphorus (P) builds up from the soils. The crops potential to extract an enriched P in soil is still lacking. Therefore, four crops were grown in three different soils with variable P levels (0 to 200 mg P/kg soil) and screened for P acquisition potentials. Total P accumulation in roots and shoot was high with enriched P levels in all soils, for example in soil A at 200 mg P/kg soil, the values were 0.44% for cucumber (Cucumis sativus), 0.40% for sunflower (Helianthus annus), and ∼0.30% for cabbage (Brassica oleracea) and 0.20% for Indian mustard (Brassica juncea). The cucumber and sunflower showed a greater biomass production (>6.0 g/pot) with enriched P levels and exhibited more prominent root characteristics, suggests more favorable for P acquisition from the P enriched soils. More prominent enhanced phosphomonoesterase and phytase activities in these crops possibly contributing to their P accumulation ability under high soil P conditions. This study shows that, cucumber and sunflower can generate high dry matter content and can accumulate greater quantity of P from the soils through different mechanisms and they can be potential candidates for phytoextraction of P from the soil P enriched areas. © 2024 Taylor & Francis Group, LLC.